Should private storage be subsidized to stabilize agricultural markets after price support schemes are removed? - Femenia, Fabienne (International Food Policy Research Institute, 2012)
Currently, there is increased focus on the methods in which public interventions stabilize agricultural markets. The subsidization of private storage is one of the options advocated. However, the efficiency of such an instrument is still being discussed and has not yet been explored in the context of imperfect information. Nevertheless, this is one of the potential sources of market fluctuations and one of the arguments in favor of a public intervention on agricultural markets. To fill this gap, our main objective in this paper is to simulate the effects of a subsidization of storage costs, aimed at stimulating private storage at the world level, on markets fluctuations following Common Agricultural Policy (CAP) reforms, so as to stimulate private storage at the world level, and to study the welfare effects of this public intervention.